Antibiotic susceptibility patterns in Rochalimaea quintana, the agent of trench fever. - Myers, W F (1984)
Rochalimaea quintana, the etiological agent of trench fever, was tested by an agar dilution method for its susceptibility to the following 14 antibiotics: penicillin G, methicillin, ampicillin, cephalothin, vancomycin, doxycycline, tetracycline, erythromycin, chloramphenicol, streptomycin, kanamycin, rifampin, colistin, and amphotericin B. The MIC of each of these antibiotics was determined. The results showed that R. quintana is susceptible in vitro to these antibiotics, with the exception of vancomycin, kanamycin, streptomycin, colistin, and amphotericin B.